Structural, elastic, electronic and thermal properties of InAs: A study of functional density - Mendoza-Estrada, Víctor; Romero-Baños, Melissa; Dovale-Farelo, Viviana; López-Pérez, William; González-García, Álvaro; González-Hernández, Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In this research, first-principles calculations were carried out within the density functional theory (DFT) framework, using LDA and GGA, in order to study the structural, elastic, electronic and thermal properties of InAs in the zinc-blende structure. The results of the structural properties (a, B0, ) agree with the theoretical and experimental results reported by other authors. Additionally, the elastic properties, the elastic constants (C11, C12 and C44), the anisotropy coefficient (A) and the predicted speeds of the sound ( , , and ) are in agreement with the results reported by other authors. In contrast, the shear modulus (G), the Young's modulus (Y) and the Poisson's ratio (v) show some discrepancy with respect to the experimental values, although, the values obtained are reasonable. On the other hand, it is evident the tendency of the LDA and GGA approaches to underestimate the value of the band-gap energy in semiconductors. The thermal properties (V, , θD yCV) of InAs, calculated using the quasi-harmonic Debye model, are slightly sensitive as the temperature increases. According to the stability criteria and the negative value of the enthalpy of formation, InAs is mechanically and thermodynamically stable. Therefore, this work can be used as a future reference for theoretical and experimental studies based on InAs.